2013
DOI: 10.1142/s0219024913500283
|View full text |Cite
|
Sign up to set email alerts
|

Real Options With Priced Regime-Switching Risk

Abstract: We develop a model of regime-switching risk premia as well as regimedependent factor risk premia to price real options. The model incorporates the observation that the underlying risky income streams of real options are subject to discrete shifts over time as well as random changes. The presence of discrete shifts is due to systematic and unsystematic risk associated with changes in business cycles or in economic policy regimes or events such as takeovers, major changes in business plans. We analyze the impact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…For the period between 1999 and 2015, we found that this method has been applied to many cases and in many different fields, from the evaluation of construction projects (Barton & Lawryshyn, 2011;Ford et al, 2002;Garg & Kumar, 2014;Jiao et al, 2007;Oppenheimer, 2002;Parthasarathy & Madhumathi, 2010;Sewalk & Dai, 2014); investments in R&D (Kumaraswamy, 1996;Ming-Cheng & Yen, 2007), in particular those by pharmaceutical companies (Gunther McGrath and Nerkar, 2004;Hartmann & Assan, 2006); the evaluation of IT (information technology) projects (Benaroch, 2002;Fichman, 2004); insurance portfolio strategies; customer relationship management (Maklan et al, 2005); the management and evaluation of intagible assets (Bhattacharya & Wright, 2005, Faiferlick et al 2004, Park et al, 2013; and the assessment of bonds and derivatives (Driffill et al, 2013;Ericsson & Reneby, 2005;Fabozzi et al, 2012, Pyo, 2008Ren-Raw et al, 2002;Singh, 2014, Tompkins, 2001). …”
Section: Resultsmentioning
confidence: 99%
“…For the period between 1999 and 2015, we found that this method has been applied to many cases and in many different fields, from the evaluation of construction projects (Barton & Lawryshyn, 2011;Ford et al, 2002;Garg & Kumar, 2014;Jiao et al, 2007;Oppenheimer, 2002;Parthasarathy & Madhumathi, 2010;Sewalk & Dai, 2014); investments in R&D (Kumaraswamy, 1996;Ming-Cheng & Yen, 2007), in particular those by pharmaceutical companies (Gunther McGrath and Nerkar, 2004;Hartmann & Assan, 2006); the evaluation of IT (information technology) projects (Benaroch, 2002;Fichman, 2004); insurance portfolio strategies; customer relationship management (Maklan et al, 2005); the management and evaluation of intagible assets (Bhattacharya & Wright, 2005, Faiferlick et al 2004, Park et al, 2013; and the assessment of bonds and derivatives (Driffill et al, 2013;Ericsson & Reneby, 2005;Fabozzi et al, 2012, Pyo, 2008Ren-Raw et al, 2002;Singh, 2014, Tompkins, 2001). …”
Section: Resultsmentioning
confidence: 99%
“…We need to take the regime shift into account to derive the value function for each regime. The procedure is exactly the same as Driffill et al (2009) and thus refer to their paper for a detailed discussion. First, for P ≥P i F 2 , firm i immediately invest in the project regardless of the realized regime.…”
Section: Follower's Problemmentioning
confidence: 99%
“…Typically, regime uncertainty is modeled in a way that parameters describing the state variables follow a Markov chain as in Driffill et al (2003), Guo et al (2005) and Hackbarth and Miao (2011). Among them, Driffill et al (2009) study the investment decision for a project whose risk premia and other exogenous parameters are subject to a stationary Markov chain. They derive a simultaneous ordinary differential equation system that can calculate an investment threshold for each regime.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Typically, regime uncertainty is modeled in a way that parameters describing the dynamics of the state variables follow Markov switching. Among them, Driffill et al (2013) study the investment decision of a project with Markov-modulated geometric Brownian motions. They derive a simultaneous ordinary differential equation system that can calculate an investment threshold for each regime.…”
Section: Introductionmentioning
confidence: 99%